Returns to job mobility: the role of observed and unobserved factors - Priscila Ferreira (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We investigate the returns to promotions and separations from firms using Portuguese linked employer-employee data. More than 90% of the total variation in wages can be ex- plained by observed and unobserved characteristics of workers and firms. Taken together, worker and firm unobserved effects explain more than half of the variation of wages for all types of job mobility. Our results suggest that promoted workers are high wage workers in high wage firms. Movers are inherently lower wage workers, in lower wage firms. However, on average, workers that find a new job within one year enter firms that pay higher wages. This is not true for workers that take more than a year to find a new job.
Keywords: 330